Quantum oscillations from surface Fermi arcs in Weyl and Dirac semimetals - Potter, Andrew C.; Kimchi, Itamar; Vishwanath, Ashvin (Nature communications, 2014)
In a magnetic field, electrons in metals repeatedly traverse closed magnetic orbits around the Fermi surface. The resulting oscillations in the density of states enable powerful experimental techniques for measuring a metal’s Fermi surface structure. On the other hand, the surface states of Weyl semimetals consist of disjoint, open Fermi arcs raising the question of whether they can be observed by standard quantum oscillatory techniques. Here, we find that the open Fermi arcs participate in unusual closed magnetic orbits by traversing the bulk of the sample to connect opposite surfaces. These orbits have anomalous features that are impossible for conventional surface states, and result in quantum oscillations that contain observable signatures of the topological character of the bulk Weyl semimetal. We also apply our predictions to the compounds Cd 3 As 2 and Na 3 Bi that were recently proposed to be three-dimensional Dirac (doubled Weyl) semimetals, and propose experimental signatures of their possible Fermi arc states. Unlike metals, Weyl and Dirac semimetals possess open discontinuous Fermi surfaces. Here, Potter et al. show how such materials may still exhibit characteristic electronic oscillations under applied magnetic fields via bulk tunnelling between Fermi arcs and predict their experimental signatures.